Evaluation of China’s ESG Policy Texts Based on the “Instrument-Theme-Subject” Framework - Liu, Yutong; Ma, Hailiang (Sustainability, 2025)
This study develops a three-dimensional evaluation framework integrating policy instruments, policy themes, and policy subjects to analyze China’s ESG (Environmental, Social, and Governance) policies. Based on 82 central government policy documents issued between 2007 and 2024, it employs content analysis, Latent Dirichlet Allocation (LDA) topic modeling, and social network analysis. The findings reveal a structural imbalance in policy instruments, with overreliance on environmental instruments and insufficient application of supply side and demand side mechanisms. Four major policy themes are identified: environmental governance, corporate responsibility and disclosure, technological innovation, and financial development. These themes show evolving priorities aligned with national strategies. Social network analysis shows weak coordination among stakeholders, with only a few central agencies driving most policies. This research contributes a systematic and quantitative approach to ESG policy evaluation, offering insights into structural shortcomings and governance fragmentation. It provides actionable recommendations for optimizing instrument use, enhancing thematic design, and improving multi-agency collaboration in ESG policymaking. This study contributes to the achievement of the United Nations Sustainable Development Goals (SDGs), particularly SDG 12 (Responsible Consumption and Production) and SDG 13 (Climate Action), by evaluating China’s ESG policies and proposing a more balanced and pragmatic policy framework.